2014
DOI: 10.1088/0029-5515/55/1/017001
|View full text |Cite
|
Sign up to set email alerts
|

APTWG: The 4th Asia-Pacific Transport Working Group Meeting

Abstract: This conference report summarizes the contributions to, and discussions at, the 4th Asia-Pacific Transport Working Group Meeting held at Kyushu University, Japan, during 10–13 June 2014. The topics of the meeting were organized under five main headings: turbulence suppression and transport barrier formation, effect of magnetic topology on MHD activity and transport, non-diffusive contribution of momentum and particle transport, non-local transport and turbulence spreading and coupling, energetic particles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Experimentally, electron cyclotron heating (ECH) effects on toroidal rotation have been studied in many tokamaks such as DIII-D 5,6 , TCV 7 , JT-60U 8,9 , AUG 10,11 , KSTAR 12,13 for various conditions, and in stellarators 14,15 as well. The direction of core toroidal rotation changes from co-current in Ohmic H-mode plasmas to counter-current in ECH H-mode plasmas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, electron cyclotron heating (ECH) effects on toroidal rotation have been studied in many tokamaks such as DIII-D 5,6 , TCV 7 , JT-60U 8,9 , AUG 10,11 , KSTAR 12,13 for various conditions, and in stellarators 14,15 as well. The direction of core toroidal rotation changes from co-current in Ohmic H-mode plasmas to counter-current in ECH H-mode plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Counter-current torque induced by micro-turbulence rather than damping by MHD activity as a physical mechanism to explain ECH effects on toroidal rotation has been discussed in Refs. 13,15. Linear stability study by gyrokinetic simulation suggests a possible transition from ion temperature gradient (ITG) turbulence to trapped elctron mode (TEM) turbulence due to the changes in temperature and density profiles induced by ECH.…”
Section: Introductionmentioning
confidence: 99%
“…So, counter-current torque induced by ECH is very high possibility to support the experiment results in this paper. Actually, it has been already observed that the central rotation changes its sign from co-to counter-current direction during high power ECH injection for the NBI+ECH plasma in LHD [32], which is the powerful evidence that the effect of ECH is not damping the rotation but driving force in counter-direction. At present, the ECH power in KSTAR is still too low.…”
Section: Discussion About Damping and Torque In Ech Plasmamentioning
confidence: 96%
“…The joint meeting was postponed due to the pandemic of COVID-19 and was held online as a virtual conference in 2021. This meeting is a series of APTWG meetings, which started at NIFS Japan in 2011 [1] and has been held every year 2011 -2018 and every two years afterward in China, Korea, or Japan [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%